Assessing the Efficiency of Takaful and Insurance Companies in Emerging Markets (Journal of Social Sciences Review, 2023)
This research was conducted to compare and contrast the effectiveness of Takaful and Conventional insurance providers in developing markets like Pakistan. This was achieved by collecting and analyzing information from the databases of four Takaful and four traditional insurance providers covering 2012-2018. The technical, cost and allocative efficiencies were determined using data envelopment analysis. Total assets and employee count were inputs, while investment income, net premium revenue, and other income were measured as outcomes. Labour and asset costs were included in determining profitability. As of 2012, Pakistan's Takaful insurance sector was considered extremely technically efficient. Conventional insurance companies were more technically efficient than Takaful insurance companies throughout the review period, with an average technical efficiency score of 0.890 compared to 0.730 for Takaful insurance companies. Pak-Qatar General Takaful was found to be the most technically efficient (0.855), Pak-Qatar Family Takaful most allocative (0.703) and cost-efficient (0.597) among all Takaful insurance firms in Pakistan. On average the technical efficiency score is 0.810, allocative efficiency 0.490 and cost efficiency 0.407. Tobit regression estimates found that investment income, size of the firm and number of employees significantly affects the efficiency scores of insurance companies. Based on the above discussion the researcher concludes that conventional and Takaful insurance companies require to improve their technical, allocative and cost efficiencies.
Keywords: Total Assets; Number of Employees; Efficiency; Net Investment Income; Net Premium Earned; Other Income